2022
DOI: 10.1155/2022/8739289
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Response to L-Arginine Alone and Combined with Different Doses of Growth Hormone-Releasing Hormone: A Systematic Review and Meta-Analysis

Abstract: Background. Arginine (ARG) can modulate growth hormone (GH) release by suppressing its endogenous inhibitory regulator, somatostatin. ARG also induces the release of the GH-releasing hormone (GHRH). This study aims to review the effects of L-arginine supplementation alone and combined with GHRH in different doses on GH secretion. Methods. In this systematic review and meta-analysis, an electronic literature search was conducted on Medline database (PubMed), Scopus, and Web of Science databases. All eligible st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Arginine supplementation also increased GH levels in elderly volunteers [8]. Several other studies have likewise demonstrated the pro-GH influence of L-arginine supplementation [9].…”
Section: Introductionmentioning
confidence: 65%
“…Arginine supplementation also increased GH levels in elderly volunteers [8]. Several other studies have likewise demonstrated the pro-GH influence of L-arginine supplementation [9].…”
Section: Introductionmentioning
confidence: 65%
“…In a 3-year follow-up on 1000 patients submitted to cardiac catheterization surgery, decreased global GABR, representing the arginine/[ornithine + citrulline] ratio, was linked to the occurrence of major adverse cardiovascular events (death, myocardial infarction, stroke) [ 13 ], a finding that was confirmed by later independent studies [ 31 , 32 ]. Our observation of a positive correlation between the GABR and fasting glucose, even after adjustment for age and gender, rather than being clinically detrimental as discussed above for adult cohorts, could be a specific and non-pathological characteristic of the young age, as arginine is an amino acid that stimulates the secretion of the growth hormone (GH) [ 33 ], a key anabolic hormone supporting children growth.…”
Section: Discussionmentioning
confidence: 99%
“…GH, especially in higher amounts, can negatively affect the human body through mitogenic effects, increasing the risk of cancer [76]. GH has also been found to reduce carbohydrate utilisation by decreasing glucose uptake, which can hinder the delivery of energy, particularly in endurance sports [77][78][79]. Collier et al [80] showed a higher maximum GH concentration in a group taking 9 g Arg than in those supplemented with 5 g Arg and placebo.…”
Section: Supplementation Of L-argininementioning
confidence: 99%